Problematika Pembelajaran PAI dalam Mengimplementasikan Kurikulum Merdeka - Himatun Aliyah; Nurfuadi (Pascasarjana IAI Nasional Laa Roiba Bogor, 2024)
When viewed from the facts in the field, the implementation of the Independent Curriculum (IKM) shows that it has not been fully realized due to various problems, including the learning of Islamic Religious Education. Learning Islamic Religious Education as a series of Islamic subjects is delivered with material taught from elementary school to tertiary level and must respond well to the Merdeka Belajar policy. Therefore, it is important to carry out an evaluation, starting with identifying obstacles so that appropriate solutions are determined. Various problems are even starting to be felt, especially by teaching staff who play an important role in the learning process. The research carried out has the aim of analyzing various problems that exist in implementing the independent curriculum. The method used is a qualitative approach using a literature review or library research method. In this case the researcher used a literature review with a narrative review. After conducting research, it was found that there were several obstacles in implementing the independent curriculum in Islamic Religious Education learning, namely obstacles originating from infrastructure, teacher conditions, student conditions, school environment, family and also the government.